THE FACTOR OF AWARENESS AND PURCHASING DECISION OF ICE CREAM BASED ON HALAL LABEL - Ulya, Muhammad Ziauddin; Rohman, Fatchur; Sunaryo, Sunaryo (Universitas Brawijaya, Indonesia, 2022)
The increasing Muslim population affects the demand for halal products. Multinational companies cannot see the current trend of Muslim consumer growth by looking at the decision-making of halal food and beverage purchases and brand awareness. This study examines the influence of religion, halal labeling, information delivery, and health considerations on brand awareness and purchasing decisions for Wall's ice cream in Malang. This research is explanatory research with 180 respondents. Data were collected using a questionnaire, and the size used a Likert scale. This paper uses the Structural Equation Model (SEM) for data analysis with the Variance Based SEM approach, commonly known as Partial Least Square (PLS). The results showed that two variables had no significant effect: exposure to information and health labels. And considering that the independent variables in this study are essential in influencing purchasing decisions, it is hoped that the results of this study can be used as a wish for further research.